(3eaghe GdSYGOI ai adSaI SjfcG (B/ s - (3LjgGf YGOd Ydi eMehOs; (3eUWai GdfTGQ (B: s ((3GdbGgQI (B: s (3LjgGf YGOd Ydi eMehO (B: s, 2011)
(3JJMOK GdQSGdI Mhd eaghe GdSYGOI ai adSaI SjfcG hgPg GdQSGdI JYO ESgGeG eJhGVY ai EKQGA GdecJHI GdYQHjI HgPG GdadjSha GdQhGbi GdeJejR abO GSJeO SjfcG CgejJg ef Yedg Ydi fTQ GdadSaI GdQhGbjI GdJi JYO GdfJGL GdQFjSi ddYUQ GdgdjfSfi hcGf SjfcG ef cHGQ GdcJGH GdCbOejf GdPi LeY Hjf GdTYQ hGdadSaI hcGf dJCKjQg ai cdG GdeLGdjf TCf cHjQ ai JGQjN GdacQ GdCQDHi hYdi GdQZe ef CgejI GdacQ GdQhGbi YfO SjfcG EdG Cfg dGjRGd ai MGLI eGSI ddeRjO ef GdOQGSGJ GdeJYebI GdJi Jdbi GdVhA Ydi GdcKjQ ef LhGfH adSaJg GdCNdGbjIs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdBOGH (B- (3bSe GdadSaIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdacQ GdQhGbi s; (3GdadSaI GdCNdGbjI s; (3eaghe GdSYGOIs